2007
DOI: 10.1016/j.bbrc.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Ca2+/calmodulin-dependent protein kinase phosphatase family (CaMKP and CaMKP-N)

Abstract: multifunctional CaMKI, II, and IV. However, the lack of specific inhibitors of these phosphatases has hampered studies on these enzymes in vivo. In an attempt to obtain specific inhibitors, we searched inhibitory compounds and found that Evans Blue and Chicago Sky Blue 6B served as effective inhibitors for CaMKP. These compounds also inhibited CaMKP-N, but inhibited neither protein phosphatase 2C, another member of PPM family phosphatase, nor calcineurin, a typical PPP family phosphatase. The minimum structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Several compounds have been reported to be PP2C (PPM1A) inhibitors based on virtual screening and modification of phosphate esters. 5,6) Cyclic phosphopeptide inhibits PP2C (Wip1 or PPM1D), and Evans Blue and its derivatives inhibit Ca 2þ /calmodulin-dependent protein kinase phosphatase (CaMKP) and its nuclear isoform CaMKP-N, which are PP2C members, 7,8) but little is known about more potent and specific inhibitors of PP2C, especially natural products.…”
mentioning
confidence: 99%
“…Several compounds have been reported to be PP2C (PPM1A) inhibitors based on virtual screening and modification of phosphate esters. 5,6) Cyclic phosphopeptide inhibits PP2C (Wip1 or PPM1D), and Evans Blue and its derivatives inhibit Ca 2þ /calmodulin-dependent protein kinase phosphatase (CaMKP) and its nuclear isoform CaMKP-N, which are PP2C members, 7,8) but little is known about more potent and specific inhibitors of PP2C, especially natural products.…”
mentioning
confidence: 99%
“…In contrast, NaF (100 mM) and EDTA (10 mM) severely inhibited the phosphatase. It is interesting that ANDS, a CaMKP-specific inhibitor [18], did not inhibit the phosphatase activity of hCaMKP-N(1–559) even at 30  μ M, a concentration at which the rat CaMKP was strongly inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, CSB and analogs have been previously found to inhibit different proteins [21,36,[42][43][44]. Thus, improvements of their inhibitor potency on Rad51 are necessary so that they might be specific enough to the recombinase protein for pharmacological studies on them.…”
Section: Discussionmentioning
confidence: 97%
“…Considering their chemical structure, these molecules could not easily enter the cell membranes, and so the nucleus, the site of Rad51 action. Nevertheless, Sueyoshi et al showed that CSB and compound 2 can be incorporated into cells to inhibit CaMKP-N expressed in those cells [36]. After verification, if CSB could not be used in its present form to improve cancer treatment, it may be a potential lead compound for developing Rad51-specific anticancer drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation